Pertanggungjawaban Pidana TNI Dalam Tindak Pidana Penganiaya - dinda lestari bunga; Muridah Isnawati (Widya Yuridika, 2022)
Criminal liability is the acceptance of all forms of punishment given to perpetrators who have committed villations (acts against the law). TNI institution which has the duty to defend the sovereignty of the nation and state, maintain the territorial integrity of the state, and maintain the safety and dignity of the indonesia nation and state. With such duties and functions, what about TNI personnel who commit serious crimes of mistreatment. The research method used is normative research which is carried out by researching library or secondary materials as the basis for research using a statutory approach related to the problems to be discussed.